Contributions of participatory forest management for sustainable livelihoods and forest conservation in Ethiopia - Zemenu Woldie; Asmamaw Alemu; Habitamu Taddese; Ewunetu Tazebew (Discover Sustainability)
Abstract The impacts of Participatory Forest Management (PFM) on forest conservation, livelihoods, and broader socio-environmental outcomes remain underexplored, with most studies being site-specific. This systematic review was based on secondary data sources retrieved from major scientific databases, including Google Scholar, ScienceDirect, Scopus, and Web of Science. A structured data extraction framework was employed to guide the review process. This systematic review synthesizes findings from 60 studies examining various dimensions of PFM in Ethiopia published between 2000 and 2024. Data were analyzed using descriptive statistics and meta-analysis approaches. Among these, 39 studies assess the impacts of PFM on forest conservation, livelihood improvements, and factors influencing its success, while the remaining six focus on other aspects of PFM. The meta-analysis of selected studies reveals that PFM significantly enhances forest density (55–70%), species diversity and plant richness (60–80%) in managed forests. Furthermore, PFM has been recognized as an effective mechanism for improving household forest income (35–60%) in intervention areas, with participating communities generally earning higher income. However, methodological inconsistencies—such as variations in forest condition metrics, follow-up durations, and livelihood indicators—limit the comparability of findings across studies. These inconsistencies reduce the ability to draw generalizable conclusions and weaken the evidence base needed to inform policy and practice. This underscores the critical need for standardized evaluation frameworks to ensure consistency in future PFM assessments. To strengthen future evaluations, standardized indicators should include ecological metrics (e.g., tree density, species richness, canopy cover) and livelihood measures (e.g., income changes, forest product use), which would improve comparability and better guide policy and donor actions.